Pharmacodynamics and Pharmacokinetics of HSK3486, a Novel 2,6-Disubstituted Phenol Derivative as a General Anesthetic - Liao, Juan; Li, Meiting; Huang, Chaoli; Yu, Yan; Chen, Yashu; Gan, Jiaqi; Xiao, Jie; Xiang, Guilin; Ding, Xizhi; Jiang, Rong; Li, Peng; Yang, Mengchang (Frontiers in Pharmacology, 2022)
Background: The purpose of this study was to characterize the novel sedative/hypnotic agent HSK3486, a 2,6-disubstituted alkylphenol analogue. Methods: The mechanism of action of HSK3486 was studied in competitive binding assays and whole-cell patch clamp assays. HSK3486 was administered by bolus intravenous injection to dogs and rats, and the loss of righting reflex as well as effects on the cardiovascular and respiratory systems were assessed. The in vitro metabolism of HSK3486 was analyzed by CYP450 genotyping and enzyme inhibition. Results: HSK3486 competed with t-butylbicycloorthobenzoate (TBOB) and t-butylbicyclophosphorothionate (TBPS) for binding to the gamma-aminobutyric acid type A (GABAA) receptor. HSK3486 potentiated GABA-evoked chloride currents at lower concentrations while activating GABAA receptor at higher concentrations. HSK3486 induced hypnosis in rats and dogs, and had a higher therapeutic index than propofol in rats. The hypnotic potency of HSK3486 was approximately 4-5 fold higher than that of propofol. HSK3486 exerted minimal effects on the cardiovascular system. Conclusions: HSK3486 is a positive allosteric regulator and direct agonist of GABAA receptor. It has a promising sedative/hypnotic effect and good in vivo pharmacokinetic properties, which justify further studies towards its clinical application.